2010
DOI: 10.1242/dev.048348
|View full text |Cite
|
Sign up to set email alerts
|

The maize SBP-box transcription factor encoded by tasselsheath4 regulates bract development and the establishment of meristem boundaries

Abstract: Plant architecture consists of repeating units called phytomers, each containing an internode, leaf and axillary meristem. The formation of boundaries within the phytomer is necessary to differentiate and separate these three components, otherwise some will grow at the expense of others. The microRNA-targeted SBP-box transcription factor tasselsheath4 (tsh4) plays an essential role in establishing these boundaries within the inflorescence. tsh4 mutants display altered phyllotaxy, fewer lateral meristems and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
158
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(161 citation statements)
references
References 36 publications
3
158
0
Order By: Relevance
“…In mutants of TASSEL SHEATH1 (Tsh1), the maize ortholog of Nl1, the bracts subtend branches and spikelet pairs in both in tassel and ear . Five Tsh genes affecting extra bract suppression have been identified in maize Chuck et al 2010). Apart from Tsh1, only Tsh4 has been cloned (Chuck et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In mutants of TASSEL SHEATH1 (Tsh1), the maize ortholog of Nl1, the bracts subtend branches and spikelet pairs in both in tassel and ear . Five Tsh genes affecting extra bract suppression have been identified in maize Chuck et al 2010). Apart from Tsh1, only Tsh4 has been cloned (Chuck et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Five Tsh genes affecting extra bract suppression have been identified in maize Chuck et al 2010). Apart from Tsh1, only Tsh4 has been cloned (Chuck et al 2010). Trd1 was proposed as an ortholog of maize Tsh1 and rice Nl1 based on evidence from conservation of synteny, mRNA expression patterns and PCR-resequencing of two mutant and a non-related wild type alleles .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, OsSPL14 (Miura et al, 2010) and OsSPL16 (Wang et al, 2012) play crucial roles in determining grain quality and yield in rice. tsh4 (tassel sheath4), a member of the maize SBP-box gene family, regulates bract development, and is required for branch meristem initiation and maintenance (Chuck et al, 2010). In addition, a series of studies have shown that SPLs play important roles in regulating plant developmental phase transition.…”
Section: Introductionmentioning
confidence: 99%